An enhanced next generation security operation center framework for information system security management - Yau, Ti Dun (2023)
Cyberattacks is becoming more common than ever. As a result, cybersecurity affects individuals and entities. It is crucial to respond rapidly to security incidents to prevent attackers from accessing vital resources as cyberattacks become more sophisticated. This research identify key areas in NGSOC, stakeholder, governance, security, technical, functionality, and threat intelligence. The propose framework is validate using a questionnaire and correlation rules utilizing threat intelligence. In order to verify the efficacy of NGSOC's detection capabilities, correlation rules is use to validate the effectiveness of threat intelligence. The framework is intended to help bridge the gap between theoretical methodologies, proprietary implementations, and standalone systems. NGSOC helps businesses prepare for intrusions. To realize their full potential, they must be properly created, deployed, integrated, evaluated on a regular basis, and enhanced over time. They boost a company's ability to fight against hackers, financial losses, and data breaches when deploy successfully.